Prevalence and causes of registered blindness in the largest federal state of Germany. Issue 8 (3rd March 2011) - Finger, Robert P; Fimmers, Rolf; Holz, Frank G; Scholl, Hendrik P N
Abstract : Aim: As no current estimates for the prevalence and causes of blindness in Germany are available, the database of Germany's largest welfare institution (covering 9.5 million people in the federal state of Northrhine) assessing eligibility for an allowance payable to blind people was used to investigate the prevalence and the specific causes of blindness and visual impairment. Methods: Data from a representative sample of 5100 cases out of 20 365 cases were extracted, entered into an electronic database and statistically analysed. Blindness and severe vision impairment were defined as visual acuity equal to or below 20/1000 and 20/400, respectively, in the better-seeing eye. Results: The mean age of the overall sample was 72±22 years and the mean visual acuity of the better seeing eye was 20/800. The prevalence of blindness and severe vision impairment in Northrhine was estimated to be 47.91 per 100 000 persons. Most registered visual impairment was due to age-related macular degeneration (AMD; 41%), followed by glaucoma (15%) and diabetic eye disease (10%). Sixty-five per cent of registered blind people were women, 56% of them over the age of 80 years. Registered children and teenagers had the relative worst visual acuity (hand movement) and patients with retinal dystrophies had the relative best visual acuity (20/200) within the whole cohort (p<0.001). Standardised prevalence of blindness and severe visual impairment for Germany is estimated to be 44.4/100.000 (57.94 for women and 30.78 for men). Conclusions: Prevalence of blindness and severe vision impairment for Germany compare well to other European countries. AMD is the most prevalent cause of registered blindness and severe vision impairment, and prevalence in women is higher. Generally, prevalence increases with age. Provision of support and welfare services need to be organised accordingly.